Propriedades de argamassas estabilizadas contendo metacaulim e EVA (Etileno Acetato de Vinila) - Souza, Letícia Sabrina de Melo (2023)
The ready mix mortar is produced in a dosing concrete plant, delivered by trucks, and is designed to remain workable for up to 72 hours, offering a significant advantage in terms of increased productivity on construction sites. With the growing use of this type of mortar, there is a need to explore the possibility of manufacturing it using waste materials in its composition, such as waste from the footwear industry specifically, EVA (Ethylene Vinyl Acetate) residue—and metakaolin. The objective of this study is to incorporate EVA waste from the footwear industry into these mortars to minimize waste and improper disposal. Simultaneously, metakaolin (MC) is employed to enhance the mechanical strength that may be reduced by the use of EVA. Furthermore, the partial substitution of cement with MC helps reduce its consumption in these mortars, thereby decreasing CO2 emissions. The study investigates the behavior of ready mix mortar with substitutions of 20%, by mass, of Portland cement with metakaolin and substitutions of fine aggregate with EVA (lightweight aggregate) at proportions of 10%, 20%, 30%, 40%, and 50%, by volume. The influence of these substitution levels on both fresh and hardened properties is evaluated, considering stabilization times of 0 hours, 48 hours, and 72 hours, and two forms of EVA incorporation: dry and pre-saturated. To achieve this, the necessary material characterization and mixture design were conducted. The mortars were then produced and subjected to tests in the fresh state (Flow table, Squeeze flow, fresh bulk density, and air content) and hardened state (apparent bulk density, capillary water absorption, tensile and compressive strength, and dynamic modulus of elasticity). Results indicate that metakaolin contributes to increased compressive and flexural strengths but also reduces the consistency of mortars in the consistency test depending on stabilization time, while increasing air content and capillary absorption. Mortars with EVA exhibit good consistency at 0 hours, as evidenced by rheological parameters. However, mortars with dry EVA incorporation above 20% displayed excessive spread and bleeding after stabilizations of 48 and 72 hours; it is noteworthy that this did not occur with mortars incorporating pre-saturated EVA, which demonstrated greater stability of fresh state properties. All mortars containing EVA showed an increase in air content, a decrease in fresh and hardened bulk density, and higher capillary water absorption compared to the reference; however, mortars with pre-saturated EVA had more favorable results than those with dry EVA incorporation. Mortars with dry EVA incorporation exhibited lower compressive and tensile strength compared to the reference mortar and the mortar with only Portland cement substitution by metakaolin. Mortars with up to 20% EVA met or approached the requirements and classifications of NBR 13281 parts 1 and 2 (2023), except for air content. However, mortars with pre-saturated EVA met the standard for both tensile and compressive strength at all EVA levels and stabilization times. The dynamic modulus of elasticity decreased for mortars with EVA. Additionally, it was observed that the studied properties in these mortars underwent modifications for different stabilization times.